Pengetahuan Masyarakat tentang Riba terhadap Perilaku Utang Piutang di Kabupaten Takalar - Rismah; Hasriana (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2021)
This study aims to determine how the knowledge and awareness of the community in the practice of debt and receivables that contain elements of usury. The method used in this research is a qualitative approach method with data collection used, namely data collection techniques by interview and documentation study. The results of this study are the practice of debt and receivables containing elements of usury carried out by some people due to a lack of knowledge and awareness in carrying out debt and credit practices regarding what usury is and what the impact of usury is, this happens because of a lack of attention from the local government which should hold socialization about how to practice money receivables that are allowed in Islam.